2013
DOI: 10.5489/cuaj.1389
|View full text |Cite
|
Sign up to set email alerts
|

Extramedullary hematopoiesis in the adrenal: Case report and review of literature

Abstract: case report E436Cite as: Can Urol Assoc J 2013;7(5-6):e436-8. http://dx

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 8 publications
1
16
0
Order By: Relevance
“…EMH can be seen in hematologic diseases such as hemoglobinopathies, myeloproliferative disorders, lymphomas, leukemia, and hemolytic anemias (4,5). EMH commonly occurs outside of the bone marrow in the reticuloendothelial system such as the spleen and liver, but can rarely be seen in organs such as brain, adrenals, pleura, bowel, and breast (7)(8)(9)(10). EMH in the adrenals is rare and is thought to be a compensatory mechanism secondary to altered hematopoiesis in patients with hemolytic disorders (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EMH can be seen in hematologic diseases such as hemoglobinopathies, myeloproliferative disorders, lymphomas, leukemia, and hemolytic anemias (4,5). EMH commonly occurs outside of the bone marrow in the reticuloendothelial system such as the spleen and liver, but can rarely be seen in organs such as brain, adrenals, pleura, bowel, and breast (7)(8)(9)(10). EMH in the adrenals is rare and is thought to be a compensatory mechanism secondary to altered hematopoiesis in patients with hemolytic disorders (8).…”
Section: Discussionmentioning
confidence: 99%
“…EMH commonly occurs outside of the bone marrow in the reticuloendothelial system such as the spleen and liver, but can rarely be seen in organs such as brain, adrenals, pleura, bowel, and breast (7)(8)(9)(10). EMH in the adrenals is rare and is thought to be a compensatory mechanism secondary to altered hematopoiesis in patients with hemolytic disorders (8). A few cases of EMH involving the adrenal glands have been reported in patients with SCD, beta-thalassemia, and hereditary spherocytosis (5,(7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
“…Karami et al 6 reported a patient with clinically palpable asymptomatic adrenal mass, whereas Calhoun et al 7 and Porcaro et al 8 reported patients with incidentally detected adrenal masses on ultrasonography. Lau et al 5 and Banerji et al 9 reported patients presenting with abdominal pain and found to have adrenal masses on imaging. All these patients remained undiagnosed after imaging or biochemical evaluation and underwent diagnostic adrenalectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with adrenal EMH are generally known to have major bthalassemia or other major hemoglobinopathies. When facing an adrenal mass, the size criteria is an important feature for making a decision (7). Masses larger than 6 cm should be considered malignant, until proven otherwise (8).…”
Section: Discussionmentioning
confidence: 99%